Olive Leaf Extract Modulates Quorum Sensing Genes and Biofilm Formation in Multi-Drug Resistant Pseudomonas aeruginosa - El-sayed, Nazly R. (Antibiotics (Basel), 2020)
Biofilm acts as a complex barrier against antibiotics. In this study, we investigated the inhibitory activities of Olea europaea (olive) leaves Camellia sinensis (green tea), Styrax benzoin, Ocimum basilicum, Humulus lupulus, Ruta graveolens, and Propolis extracts on the biofilm formation, pyocyanin production, and twitching motility of Pseudomonas aeruginosa isolates. Moreover, we investigated the effect of olive leaf extract on the transcription of some biofilm related genes. A total of 204 isolates of Pseudomonas were collected from different Egyptian hospitals. A susceptibility test, carried out using the disc diffusion method, revealed that 49% of the isolates were multidrug-resistant. More than 90% of the isolates were biofilm-forming, of which 26% were strong biofilm producers. At subinhibitory concentrations, green tea and olive leaf extracts had the highest biofilm inhibitory effects with 84.8% and 82.2%, respectively. The expression levels of lasI, lasR, rhlI, and rhlR treated with these extracts were significantly reduced (p < 0.05) by around 97–99% compared to untreated isolates. This study suggests the ability of olive leaf extract to reduce the biofilm formation and virulence factor production of P. aeruginosa through the down regulation of quorum sensing (QS) genes. This may help in reducing our dependence on antibiotics and to handle biofilm-related infections of opportunistic pathogens more efficiently.